Concomitant Production of Lipids and Carotenoids in Rhodosporidium toruloides under Osmotic Stress Using Response Surface Methodology - Singh, Gunjan; Jawed, Arshad; Paul, Debarati; Bandyopadhyay, Kalyan K.; Kumari, Abha; Haque, Shafiul (Frontiers in Microbiology, 2016)
As a replacement to existing fossil fuels, biofuels, have proven their worth; however, their widespread use is limited due to inconsistent yields, higher costs and poor productivity. An oleaginous yeast, Rhodosporidium toruloides has been reported to accumulate substantial amounts of lipids (that can be converted to biofuels) and therefore, it was selected for study and optimization. Apart from lipids, R. toruloides is also reported to produce carotene that can be used as a therapeutic agent. In this study, the culture medium was statistically modelled and optimized for concomitant production of lipids and carotenoids and for improving and maximizing the productivity of lipids as well as carotenes. The two metabolites were expressed differentially in the growth cycle of this organism. Culture medium components were simultaneously varied at 5 different levels using statistical modelling employing RSM. Osmotic stress was introduced in order to simulate saline conditions and optimize the production process to be used in conditions with high salt contents. In this study, we demonstrate 36.2% (w/v) lipid production and 27.2% (w/v) carotenoid production, under osmotic stress with high salt concentrations, for the first time.